Implementation of Artificial Intelligence (AI) Role-Based NormalizationMap of Demographic Data of Prospective Students of SD Al-Imam Islamic School (AI IS) - Bajsair, Faik (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research examines the application of rule-based Artificial Intelligence (AI) to address demographic data inconsistency among prospective students at SD Al-Imam Islamic School. Unstructured applicant data, particularly in the village/sub-district address column, often impedes efficient analysis and strategic decision-making. By implementing a dictionary-based normalization technique (normalizationMap) using Google Apps Script, this study aims to enhance data quality and minimize input inconsistencies. The role-based approach ensures that various input formats are mapped to a predefined standard. The implementation results demonstrate a significant improvement in the accuracy of the address data, directly supporting more precise demographic visualization. This practical and effective AI solution facilitates data-driven decision-making for future student enrollment strategies, showcasing a tangible contribution to data management within a limited-resource educational environment.